E-AHPBA-ESSO-ESSR Innsbruck consensus guidelines for preoperative liver function assessment before hepatectomy - Primavesi, Florian; Maglione, Manuel; Cipriani, Federica; Denecke, Timm; Oberkofler, Christian E; Starlinger, Patrick; Dasari, Bobby V M; Heil, Jan; Sgarbura, Olivia; Søreide, Kjetil; Diaz-Nieto, Rafael; Fondevila, Constantino; et al. (The British journal of surgery, 2023)
Posthepatectomy liver failure (PHLF) contributes significantly to morbidity and mortality after liver surgery. Standardized assessment of preoperative liver function is crucial to identify patients at risk. These European consensus guidelines provide guidance for preoperative patient assessment.A modified Delphi approach was used to achieve consensus. The expert panel consisted of hepatobiliary surgeons, radiologists, nuclear medicine specialists, and hepatologists. The guideline process was supervised by a methodologist and reviewed by a patient representative. A systematic literature search was performed in PubMed/MEDLINE, the Cochrane library, and the WHO International Clinical Trials Registry. Evidence assessment and statement development followed Scottish Intercollegiate Guidelines Network methodology.Based on 271 publications covering 4 key areas, 21 statements (at least 85 per cent agreement) were produced (median level of evidence 2− to 2+). Only a few systematic reviews (2++) and one RCT (1+) were identified. Preoperative liver function assessment should be considered before complex resections, and in patients with suspected or known underlying liver disease, or chemotherapy-associated or drug-induced liver injury. Clinical assessment and blood-based scores reflecting liver function or portal hypertension (for example albumin/bilirubin, platelet count) aid in identifying risk of PHLF. Volumetry of the future liver remnant represents the foundation for assessment, and can be combined with indocyanine green clearance or LiMAx® according to local expertise and availability. Functional MRI and liver scintigraphy are alternatives, combining FLR volume and function in one examination.These guidelines reflect established methods to assess preoperative liver function and PHLF risk, and have uncovered evidence gaps of interest for future research.Liver surgery is an effective treatment for liver tumours. Liver failure is a major problem in patients with a poor liver quality or having large operations. The treatment options for liver failure are limited, with high death rates. To estimate patient risk, assessing liver function before surgery is important. Many methods exist for this purpose, including functional, blood, and imaging tests. This guideline summarizes the available literature and expert opinions, and aids clinicians in planning safe liver surgery.
Vorab online veröffentlicht: 12. August 2023
Gesehen am 15.11.2023